The Influence of Promotion, Content Marketing, and Impulse Buying on The Purchase Decision of K-Pop Boy Group NCT Merchandise at The Flurry Station Kediri Store NCT Merchandise at The Flurry Station Kediri Store - Cahyantik, Irma Dewi; Raharjo, Itot Bian (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The objective of this research is to analyze the influence of promotional activities, marketing content, and impulse purchasing behavior on consumer purchasing decisions regarding NCT K-pop merchandise at Flurry Station. Design/Method/Approach : A quantitative approach was applied to this study. Research approach with causality technique with multiple linear regression data analysis technique. Research Finding : The study finds that promotion, content marketing, and impulse buying positively and significantly affect purchase decisions, with these variables collectively influencing purchase decisions. Theoretical contribution/Originality : This research contributes to the understanding of promotion, content marketing, and impulse buying on the purchasing behavior of collectible products in a distributor. Practitionel/Policy implication : This research can be an overview in creating marketing strategies, as well as understanding consumer needs and expectations in encouraging repeat purchases. Research limitation : This research only focuses on promotion, content marketing, impulse buying and purchase decisions.